Development and Inequality: between the old and the new paradigms - Gamero Requena, Julio (2006)
Within the framework of an exposition on the successive conceptions of development, in relation to the policies applied in Latin America, the article presents the most outstanding points of John Rawls's theory of distributive justice, and Amartya Sen's philosophy on development. understood as an expansion of freedoms.